Signal mining of adverse events of proteasome inhibitors in multiple myeloma based on FAERS - Peng, Yuan; Zhou, Yuying; Shu, Kaisen; Jia, Xu; Zhong, Yan (Frontiers in Pharmacology, 2024)
Objective: To mine and analyze adverse events related to proteasome inhibitors in multiple myeloma based on the U.S. Adverse Event Reporting System (FAERS), providing references for rational clinical medication.Adverse events(AEs) data related to multiple myeloma proteasome inhibitors were collected from FAERS from the first quarter of 2010 to the first quarter of 2024. Signal mining of AEs was conducted using the reporting odds ratio method and Bayesian confidence propagation neural network.Results: A total of 7208 reports for bortezomib, 5189 for carfilzomib, and 8776 for ixazomib were collected, with corresponding AE signals of 339, 280, and 287, respectively, involving 22, 20, and 22 System Organ Class (SOC). The report information for the three drugs tends to be consistent: more cases in males than females; with age predominantly over 65 years old; AEs mostly occur within six months of medication; the outcomes primarily consist of hospitalization, prolonged hospital stay, and other serious adverse events; the primary reporting country is the United States.The most affected SOCs were infections and infestations, general disorders and administration site conditions, and blood and lymphatic system disorders.The overall distribution of adverse events for the three multiple myeloma proteasome inhibitors is consistent, but there are certain differences in specific AE signal characteristics, which should be noted in clinical applications.